2007
DOI: 10.1073/pnas.0700642104
|View full text |Cite
|
Sign up to set email alerts
|

SHP-2 tyrosine phosphatase inhibits p73-dependent apoptosis and expression of a subset of p53 target genes induced by EGCG

Abstract: Green tea polyphenol, epigallocatechin-3-gallate (EGCG) differentially regulates the cellular growth of cancer cells in a p53-dependent manner through apoptosis and/or cell cycle arrest. In an effort to further elucidate the mechanism of differential growth regulation by EGCG, we have investigated the role of the tyrosine phosphatase, SHP-2. Comparing the responses of mouse embryonic fibroblasts (MEFs), expressing either WT or functionally inactive/truncated SHP-2, we find that inactivation of SHP-2 remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 45 publications
3
41
1
Order By: Relevance
“…Amin et al [46] have identified SHP-2 (a kind of tyrosine phosphatase) as a protective factor of cells lacking functional p53 from EGCG-induced apoptosis. Moreover, they revealed a number of targets for EGCG-induced apoptosis which were expressed in the absence of functional p53.…”
Section: Inhibition Of the Cancer Progression Stage By Egcgmentioning
confidence: 99%
“…Amin et al [46] have identified SHP-2 (a kind of tyrosine phosphatase) as a protective factor of cells lacking functional p53 from EGCG-induced apoptosis. Moreover, they revealed a number of targets for EGCG-induced apoptosis which were expressed in the absence of functional p53.…”
Section: Inhibition Of the Cancer Progression Stage By Egcgmentioning
confidence: 99%
“…Still, a number of p53 mutant proteins can associate with p63 and p73, blocking their transcriptional activity and thus contributing to the malignant phenotype of cancer cells (9)(10)(11). Activation of p73 in human cancer can produce substantial cytotoxic effect even in the cells lacking p53 (12)(13)(14)(15)(16), which allows considering p73 as a separate anticancer drug target. We decided to search for small molecules that release suppressor activities of the p53 family members blocked by mutant p53.…”
mentioning
confidence: 99%
“…6E, p73 activation kinetics was different, but rather reciprocal, from that of p53, suggesting that distinct mechanisms may underlie EGCG-induced p53 and p73 activation. Two reports show that p73 is activated by EGCG (9,40). One of these studies showed that reactive oxygen species produced by EGCG is the factor that activates p73 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Two reports show that p73 is activated by EGCG (9,40). One of these studies showed that reactive oxygen species produced by EGCG is the factor that activates p73 (9). Elucidation of this mechanism is one of our future goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation